Community Participation in Development of Ecotourism in Taman Beach, Pacitan District - Putra, Heru Wiwoho Supadi; Hakim, Abdul; Riniwati, Harsuko; Leksono, Amin Setyo (Journal of Indonesian Tourism and Development Studies, 2019)
Taman Beach as one of the superior tourist destinations in Pacitan has now begun to develop. The development of Taman Beach tourism object is inseparable from the efforts which are initiated by the Group of Turtle Rescue Society for Tourism "Taman Ria" which develops turtle conservation activities through the concept of community-based ecotourism. Local people have also developed tourist attractions such as flying fox and swimming pools to attract tourists to visit it and a portion of the tourism incomes for the funding of turtle conservation activities. However, in the development process, there are problems such as the low level of community participation and the lack of management of tourist object that is integrated with the local community.This study aims to analyze the role and level of community participation in supporting the development of community-based ecotourism in the Taman Beach area. The method used in this research is descriptive quantitative. Quantitative data analysis using the Multidimensional Scaling (MDS) approach. Data collection is done by using questionnaires and observations in the field. The variables studied included the dimensions of planning, management, monitoring, and supervision. The results of the study indicate that the involvement of local communities in the development of ecotourism does not support sustainability, with an average sustainability index value of 46.864. The level of community participation according to Arnstein's participatory ladder from the aspect of planning and management aspects has reached the level of placement participation in the tokenism category (accepting the provisions). Whereas from the aspect of monitoring and controlling has reached the level of consultation participation in the tokenism category (accepting the provisions). The results of the analysis show that policy strategies are needed to increase community participation through increasing community roles and responsibilities in planning, management, monitoring, and controlling. Keywords: community based, ecotourism, multidimensional scaling